North Pacific Gyre Oscillation and the occurrence of western North Pacific tropical cyclones - Zhang, W.; Leung, Yee-Hong; Min, J. (American Geophysical Union, 2013)
This study examines links between the North Pacific Gyre Oscillation (NPGO) and the occurrence of tropical cyclones (TCs) in the western North Pacific (WNP) at both interannual and decadal scales. The major findings are summarized as follows: (1) NPGO makes significant impacts on the WNP TC frequency at both interannual and decadal time scales. The impacts of NPGO on the TC activity are more profound than those exerted by the Pacific Decadal Oscillation and the El Niño Southern Oscillation. (2) Niño 3 plays a more important role than Niño 3.4 and Niño 4 in modulating the decadal WNP TC activity. (3) Positive low-level relative vorticity and weak zonal vertical wind shear are responsible for the increase in the WNP TC activity in negative NPGO phases. This study indicates that the NPGO and Niño 3 indices should be key factors for building a scheme for decadal prediction of occurrences of WNP TCs. Key Points NPGO makes significant impacts on the inter-annual and decadal WNP TC frequency The impacts of NPGO on TC activity are more profound than those by PDO and ENSO Nino 3 plays a more important role in decadal WNP TCs than Nino 3.4 and Nino 4 ©2013. American Geophysical Union. All Rights Reserved.